(untitled) - Dewey, Barbara I. (Chicago, 1993)
Chapter 1 Meetings, productivity, and innovation; Chapter 2 Effective meetings: basic ingredients; Chapter 3 Effective communication in the meeting environment; Chapter 4 Alternatives to traditional meetings: new methods of collaboration.
Keywords: Library meetings